Salivary flow analysis and oral injuries in homebound older persons care - Flávia Mussatto; Fernanda Grisotti Wonsovicz; Bruno Bonacir Coelho; Daniela de Rossi Figueiredo (RGO: Revista Gaúcha de Odontologia)
ABSTRACT Objective: Test the association between salivary flow and oral conditions in homebound older persons in Palhoça, Santa Catarina. Methods: This cross-sectional observational study included older persons aged >60 years, confined to their homes, and registered in the Better in Home program. Home visits were conducted with Community Health Agents between December 2019 and March 2020 and between December 2021 and March 2022. Were considered low flow when stimulated salivary flow rates <0.7 ml/min and unstimulated rates <0.1 ml/min. Socioeconomic variables, DMFS index, Visible Plaque Index, and mucosal alterations were included. Pearson’s Chi-squared and Student’s t-test were used (α=5%). Results: The sample included 44 older persons. The prevalence of low-stimulated salivary flow was 65.9% (95% CI: 50.3-78.7), while low-unstimulated salivary flow was 27.3% (95% CI: 15.8-42.8). Two-thirds were aged 60–79 years, and 56.8% were female. Daily use of 5-10 medications was reported by 63.6%, with antihypertensives (88.6%), diuretics (36.4%), and antidiabetics (34.1%) being most common; 59.2% used at least one combination of these. Visible plaque was present in 96.0%, mean DMFS was 125.9, two-thirds exhibited mucosal lesions, and 52.3% required dental prostheses. Low-stimulated salivary flow was associated with older age (p=0.023), use of antidiabetics (p=0.037), and mucosal alterations (p=0.036). Low unstimulated salivary flow was associated with a higher mean of caries (p=0.036). Conclusion: Low salivary flow, stimulated or unstimulated, was associated with oral ulcerations, gingivitis, caries, advanced age, and medication use, highlighting specific strategies for the oral health needs of homebound older persons.